Efektifitas belajar gerak dasar berbasis permainan tradisional Aceh untuk siswa sekolah dasar - Saputra, Hendra; Aspar, Muhammad (Motion: Journal Research of Physical Education, 2024)
The primary objective of the study is to assess the efficacy of teaching fundamental movements using traditional Acehnese sports among elementary school children. This study employs descriptive quantitative research methodologies. The participants in this study consisted of primary school pupils from upper and lower socioeconomic classes. The study included 35 students, and its efficacy was tested. The findings of this study indicate that kids in primary school might enhance their fundamental motions by utilizing traditional Acehnese games. This can be demonstrated by the disparity between the average pretest and posttest scores, which amounts to 19.34286. This discrepancy reflects the variation in scores obtained from the fundamental movement ability test. Moreover, the key finding from this data set is the computed t value of 68.864 with degrees of freedom (df) equal to 34, resulting in an associated table value of 2.032. When comparing the estimated t value to the t table, it is found that the sig value or the p-value is 0.000, which is greater than 0.05. Therefore, the null hypothesis (H0) is discarded. Consequently, there are disparities in the outcomes of the fundamental movement aptitude tests conducted on the experimental population before (pretest) and following (posttest) therapy utilizing the basic motion learning model derived from traditional Acehnese games. The novel aspect of acquiring fundamental movements through traditional Acehnese games serves as both a means of learning these motions and a platform for understanding the inherent values inside these games